1987
DOI: 10.1111/j.1943-278x.1987.tb00061.x
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Predictive Model of Suicidal Ideation and Behavior: Some Preliminary Data in College Students

Abstract: Within a multivariate statistical design, the relationship of various interpersonal, emotional, and cognitive variables to suicidal ideation and behavior in college students was examined. A total of 158 subjects (58 males, 100 females) completed self-report measures of life stress, faulty cognitions, loneliness, depression, hopelessness, family cohesiveness, adaptive reasons for living, and suicidal ideation and behavior. The results of a multiple-regression analysis, forward-inclusion algorithm, indicated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
149
0
12

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(175 citation statements)
references
References 30 publications
14
149
0
12
Order By: Relevance
“…In Portugal, to the best of our knowledge, no study has examined the impact of suicide on suicide risk of individuals bereaved by suicide, namely regarding the variables that might be related to suicidal ideation and risk, such as distress. Suicidal ideation is considered a key indicator of suicide risk (Ash, 2006;Bolognini, Plancherel, Laget, & Halfon, 2003;Bonner & Rich, 1987;Joiner et al, 2005;Linehan, 1981). Thus, identifying factors potentially contributing to suicidal ideation in family members bereaved by suicide is critical for the reduction and prevention of suicide thoughts and the transition from ideation to suicide (Kessler, Borges, & Walters, 1999;Mann et al, 2005).…”
mentioning
confidence: 99%
“…In Portugal, to the best of our knowledge, no study has examined the impact of suicide on suicide risk of individuals bereaved by suicide, namely regarding the variables that might be related to suicidal ideation and risk, such as distress. Suicidal ideation is considered a key indicator of suicide risk (Ash, 2006;Bolognini, Plancherel, Laget, & Halfon, 2003;Bonner & Rich, 1987;Joiner et al, 2005;Linehan, 1981). Thus, identifying factors potentially contributing to suicidal ideation in family members bereaved by suicide is critical for the reduction and prevention of suicide thoughts and the transition from ideation to suicide (Kessler, Borges, & Walters, 1999;Mann et al, 2005).…”
mentioning
confidence: 99%
“…Beck et al (1979) suggested that modification of dysfunctional beliefs and self-defeating thought patterns is an effective treatment for loneliness. Other researchers have concurred with this strategy (Blai, 1989;Brage et al, 1993;Rich & Bonnet, 1987). However, cognitive therapy should target the alleviation of loneliness and not simply make one cognitively adept at coping with the problem.…”
Section: Lonelinessmentioning
confidence: 95%
“…Bonner and Rich & Bonnet, 1987) have provided evidence that social support moderates the relation ship between life stress and depression, and Bamett and Gotlib (1988) showed that, even when the effects of concurrent symptoms are controlled, low social integration may be involved in the etiology of depression. Leary (1990) also concluded that, although not all depression is caused by social exclusion, social exclusion generally causes depression.…”
Section: Shyness and Lonelinessmentioning
confidence: 99%
See 1 more Smart Citation
“…Suicide ideation can be operationalised as ranging from relatively mild, general thoughts about death and wishes that one was dead to serious ideation about specific plans and means of taking one's life. It may also be considered a primary marker for the risk of more suicidal behaviours (Bonner & Rich, 1987;Reynolds, 1991a;Shea, 1998). Schotte and Clum (1982) as well as Bonner and Rich (1987) found a relationship between the frequency of suicide ideation and the likelihood of attempts at suicide, but Reynolds (1991a) found that a larger proportion of individuals think about suicide than actually attempt suicide.…”
Section: Theoretical Backgroundmentioning
confidence: 99%